Os caixeiros no Ceará: trabalho e educação na Revista Phenix – 1891 – 1916 - Oliveira, Francisco de Assis Santos de (2005)
The theme of associativism and workers' experiences, including social relations, in the world of work, has been configured as a significant objective in the field of social history, in which the present study on clerks in Ceará is inserted, seeking to discuss, with reading of Phenix Magazine, the meaning of Instruction and Education for Work, the customs, the readings and the social relations built by the "young men of commerce", in the first decades of the last century.